PERANCANGAN KONSEP IDEAL DESA WISATA DI DESA CIBINUANG KABUPATEN KUNINGAN - Rahajaan, Jerry Dounald; Kurniadi, Erik; Yusuf, Fahmi; Darmawan, Erlan; Herawati, Resma Mega (Empowerment : Jurnal Pengabdian Masyarakat, 2020)
Cibinuang Village is an area located in Kuningan District, Kuningan Regency. Cibinuang Village has many and varied natural resources. In the process of development activities Cibinuang tourism village has not fully used the detailed concept of tourism. The development of the concept of tourism in the Village of Cibinuang did not escape the existence of adequate natural resources and quality human resources. The availability of natural resources and their use in Cibinuang Village, even if simple and limited, will be able to improve the quality of the village and be a source of increased human resources for the community. In terms of improving the economy, knowledge and attractiveness of tourism. Efforts to design the concept of a tourist village, in improving the ability of rural communities in the field of tourism required a whole design concept to make it happen. It is understood together that one of the concrete manifestations of Higher Education gait besides education and research is Community Service and Service activities, this is in accordance with what is mandated in Law No. 20 of 2003 concerning National Education System article 24 (2) which states; "Universities have the autonomy to manage their own institutions as centers for the administration of higher education, scientific research, and community service." As a concrete step Faculty of Computer Science, Kuningan University with the core of Visual Communication Design, trying to respond to the needs of the community (Cibinuang Village) of the importance of developing Tourism Villages by doing Community Service with the title of the activity "The Concept of Designing Tourism Villages in Cibinuang Area Kuningan District of West Java Province" . Referring to the background of existing problems, problem solving is needed for the purpose of this activity are: Designing the concept of village tourism design for the people of Cibinuang Village, Kuningan Regency, to utilize natural resources in the area, which include: Hot Springs, Campgrounds, Sacred / Ancient Tombs. Creating a Tourism Village Study Plan for Cibinuang Village Community, Kuningan District to realize the Village program.Desa Cibinuang merupakan salah satu daerah yang terletak di Kecamatan Kuningan Kabupaten Kuningan. Desa Cibinuang memiliki sumberdaya alam yang banyak dan berfariasi. Dalam proses kegiatan pengembangan Desa wisata Cibinuang belum sepenuhnya menggunakan konsep wisata yang terinci. Perkembangan konsep pariwisata di Desa Cibinuang tidak luput dari adanya sumberdaya alam yang memadai dan sumber daya manusia yang berkualitas. Ketersediaan sumber alam dan pemanfaatannya di Desa Cibinuang, sekalipun sederhana dan terbatas, akan dapat meningkatkan kualitas desa serta menjadi sumber peningkatan SDM bagi masyarakat. Dalam hal peningkatan ekonomi, pengetahuan, dan daya tarik pariwisata. Upaya perancangan konsep desa wisata, dalam peningkatan kemampuan masyarakat desa dalam bidang pariwisata diperlukan suatu konsep desain yang utuh untuk mewujudkannya. Dipahami bersama bahwa salah satu wujud nyata kiprah Perguruan Tinggi selain pendidikan dan penelitian adalah kegiatan Pengabdian dan Pelayanan kepada Masyarakat, hal ini sesuai dengan apa yang diamanatkan dalam UU No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional pasal 24 (2)  yang menyatakan ; “Perguruan tinggi memiliki otonomi untuk mengelola sendiri lembaganya sebagai pusat penyelenggaraan pendidikan tinggi, penelitian ilmiah, dan pengabdian kepada masyarakat”. Sebagai langkah kongkrit Fakultas Ilmu Komputer Universitas Kuningan dengan core Desain Komunikasi Visual, mencoba untuk merespon kebutuhan masyarakat (Desa Cibinuang) akan pentingnya pengembangan Desa Wisata dengan melakukan Pengabdian Kepada Masyarakat dengan judul kegiatan “Konsep Perancangan Desa Wisata Di Daerah Cibinuang Kabupaten Kuningan Provinsi Jawa Barat”. Mengacu pada latar belakang permasalahan yang ada maka dibutuhkan pemecahan masalah untuk tujuan kegiatan ini adalah:  Merancang konsep Desain desa wisata bagi Masyarakat Desa Cibinuang, Kabupaten Kuningan, untuk memanfaatkan sumber daya alam yang ada di daerahnya, yaitu meliputi: Sumber Air Panas, Bumi Perkemahan, Makam Keramat/Kuno. Membuat StudyPlan Desa Wisata bagi Masyarakat Desa Cibinuang, Kabupaten Kuningan untuk mewujudkan program Desa.